2019
DOI: 10.4314/evj.v23i1.1
|View full text |Cite
|
Sign up to set email alerts
|

Carcass characteristics of draught cattle released for beef in Eastern Ethiopia

Abstract: Most cattle used for beef production in Ethiopia are Zebu breeds. Usually released for beef when they are aged for plowing and in poor body condition. However, there is little available information on carcass yield and percentage earned from these cattle. Therefore, the study was conducted to evaluate the carcass yield and the percentage of cattle released for beef after used in draught power. This study used 280 heads of male indigenous draught cattle released for beef. Each cattle were randomly measured for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…Some studies suggest that exercise can lead to an increase in the size and weight of the heart in animals due to cardiac hypertrophy [47] [48] [49]. The heart weight in the current study was similar to that reported by Mengistu et al [26], who reported 0.7 ± 0.05 kg for Ethiopian highland Zebu bulls, but lower than the heart weight of Zebu breeds (1.033 kg) [50], and oxen released for beef after draught service (1.01 kg) [27].…”
Section: Draught Work Hour Effects On Offal'ssupporting
confidence: 88%
See 1 more Smart Citation
“…Some studies suggest that exercise can lead to an increase in the size and weight of the heart in animals due to cardiac hypertrophy [47] [48] [49]. The heart weight in the current study was similar to that reported by Mengistu et al [26], who reported 0.7 ± 0.05 kg for Ethiopian highland Zebu bulls, but lower than the heart weight of Zebu breeds (1.033 kg) [50], and oxen released for beef after draught service (1.01 kg) [27].…”
Section: Draught Work Hour Effects On Offal'ssupporting
confidence: 88%
“…Despite, Ethiopia's agricultural system relies on animal draught power [24] [25], there was no scientific evidence concerning how much using animals for draught power can affect the physical characteristics of carcasses specific to the Hararghe highland breed, with the exception of Mengistu et al [26], who have attempted to address the carcass characteristic concern with limited variables in Ethiopian highland Zebu. Ewonetu and Ashenafi [27] suggested that assessing carcass characteristics of cattle following draught service is crucial, to enhance the productivity of the carcass for economic reasons [28] in the Ethiopia context. Thus, the objective of the study was to evaluate the impact of draught service on carcass characteristics, meat output potential and its distribution along prime cuts in Hararghe highland bulls fed on a net energy requirement basis.…”
Section: Introductionmentioning
confidence: 99%
“…For the former, we used values of crop production in the HarvestChoice database (International Food Policy Research Institute, 2020) to estimate the net present value (NPV) of prioritized planning units over a 40-year period, applying a discount rate of 5% and assuming a profit margin of 20% (Strassburg et al, 2020). For pastureland, the opportunity cost was estimated based on cattle stocking levels in the Gridded Livestock of the World v2.0 dataset (Gilbert et al, 2018), combined with average animal ages, weights and values of carcases at slaughter in Ethiopia (Senbeta & Megersa, 2019;Tefera et al, 2019). Again, the NPV for each prioritized planning unit was estimated over a 40-year horizon.…”
Section: Measuring the Impacts Of Restorationmentioning
confidence: 99%